Factors associated with inter-farm spread of porcine epidemic diarrhea (PED) in Kagoshima and Miyazaki Prefectures, Japan - Makita, K.; Toyomaki, H.; Sekiguchi, S.; Sasaki, Y.; Sueyoshi, M. (2015)
Purpose: In October 2013, an outbreak of porcine epidemic diarrhea (PED) was confirmed in Japan. The disease spread countrywide, and more than 400,000 pigs died in total as of March 22, 2015. The present study was conducted to understand the factors having caused such a wide inter-farm spread. Methods: Kagoshima and Miyazaki Prefectures, the main pig production areas of Japan, were selected as study sites. A spatio-temporal analysis was conducted to detect disease clustering using SaTScan version 9.3.1, selecting week as time unit and Bernoulli model, with anonymized data on farm size, farm types, administrative units, and date of onset provided by both prefectures (709 and 506 farms in Kagoshima and Miyazaki). Univariate and multivariable survival analyses were performed using the data in R version 3.0.2. Separately, a case-control postal survey was conducted on 78 infected (infection confirmed between Dec 2013 and Aug 2014) and 91 non-infected pig farms in Kagoshima and Miyazaki Prefectures for detailed biosecurity measures, and univariate analysis was performed. Results: Accumulated incidence rate at farm level was 23.6% in Kagoshima and 15.6% in Miyazaki as of July 24, 2014. SaTScan found three disease clusters: Kanoya (16.9km, Dec 3rd 2013 to Feb 13th 2014, Kagoshima), Miyakonojo (one city, radius not calculated, Jan 10th to 30th), and northern Miyazaki (32.4km, Mar 14th to Apr 3rd, Miyazaki). In survival analysis, survivorship was significantly lower (7.5) in integrated farms which have susceptible suckling pigs and visit slaughterhouses, than grow-finisher farms (8.2, p < 0.01). In all farm types, there were significant negative associations between survivorship, and farm size and farm density (both p < 0.01). Use of two specific abattoirs, use of communal compost depots, and not disinfecting a floor mat of track transporting pig excrement/compost were significant risk factors for PED. Conclusions: Our study identified two modes of transmission: slaughterhouses (common source infection), and compost management. Cleaning and disinfection associated with these pathways would reduce the chance of PED transmission. Relevance: This is relevant to infection control.